Knowledge, attitude, and practice of One Health and zoonotic diseases among multisectoral collaborators in Bhutan: Results from a nationwide survey. - Bir Doj Rai; Tenzin Tenzin; Dorji Tshering; Narapati Dahal; Gizachew A Tessema; Lin Fritschi; Sylvester Nyadanu Dodzi; Gavin Pereira (PLOS Global Public Health)
The One Health concept is increasingly employed to combat zoonotic diseases. This study assessed the knowledge, attitudes, and practices regarding One Health and zoonotic diseases among key sector professionals to identify gaps and opportunities for enhancing One Health strategies in Bhutan. A cross-sectional, facility-based study was used to conduct a nationwide online questionnaire survey using a validated and pre-tested questionnaire among professionals from the Ministry of Health, the Ministry of Agriculture and Livestock, and universities. Descriptive and summary statistics were calculated. Respondents were categorised into binary groups based on their knowledge, attitude, and practice scores relative to the mean. Multivariable logistic regression analyses were conducted to identify the demographic factors associated with knowledge, attitudes, and practices regarding One Health and zoonotic diseases. The survey achieved a 35% response rate, with 964 responses. The majority of respondents demonstrated above-average knowledge (63%), attitudes (50%), and practices (66%) regarding One Health. Professionals with master's degree or higher (Adjusted Odds Ratio [AOR] = 2.39; 95% Confidence Interval [CI] = 1.16-5.12) were more likely to have above-average knowledge. Regarding zoonotic diseases, approximately half of the respondents had above-average knowledge (51%), attitudes (52%), and two-thirds (66%) had above-average practices. Professionals with mid-level job experience (6-10 years; AOR = 2.13; 95% CI = 1.37-3.30 and 11 to 15 years; AOR = 2.11; 95% CI = 1.31-3.40) were more likely to possess above-average knowledge. Gaps in training, communication, funding, research, and collaborations were identified. Targeted educational interventions, enhanced communication, strengthened collaboration, expanded research, and improved funding are essential for improving One Health approaches and zoonotic disease prevention and control in Bhutan. Our study findings provide valuable insights that can inform global efforts to enhance One Health systems, particularly in regions where resources are limited but disease risks are significant.